Students’ Perception and Performance Regarding Structured Query Language Through Online and Face-to-Face Learning - Elalouf, Amir; Edelman, Arik; Sever, Dafna; Cohen, Shaked; Ovadia, Reut; Agami, Omer; Shayhet, Yulia (Frontiers in Education, 2022)
This study explores the Structured Query Language (SQL) learners’ perceptions in online and face-to-face learning regarding the role of the instructor, clarity in lesson delivery and understanding, and concerns about the shift in learning mode. In parallel, we evaluate the performance of online and face-to-face SQL learners in the final examination. The COVID-19 pandemic has forced educational institutes to shift their activities online. Thus, online learning has been accepted during the pandemic and gradually evolving. The literature on online and face-to-face learning has evaluated limited variables. Yet, in online and face-to-face learning, critical parameters concerning the SQL learners’ perceptions about the role of instructors have not been explored. The present study surveyed the final-year students learning medium-level SQL courses at Bar-Ilan University Israel and the College of Management Academic Studies Israel. Survey questionnaires included demographic information, online learning experience, online learning sources, and ten questions about the learners’ concerns of shifting, effectiveness, adequate instructions, the lecturer’s clarity during instruction, clear understanding of the lesson, instructor’s tools, instructor’s availability, satisfactory response, learning independence, and spending extra time in online and face-to-face learning, separately. This study included 102 online learners and 95 face-to-face learners. All the online learners used Zoom and WhatsApp, and the face-to-face learners used Gmail and WhatsApp. Both online and face-to-face learners were significantly satisfied with the lecturer’s performance, especially with the clarity in lecture delivery, instructor availability, and satisfactory response from the lecturer. In addition, online learners agreed upon the effective way of learning, clear understanding of the lesson, independence, and spending extra time. In contrast, face-to-face learners were more satisfied with the tools of the lecturer and dissatisfied with the dependence on the lecturer. Female students attending face-to-face learning were more concerned about the shift in the mode of learning. Further, online learners performed better in written examinations and face-to-face learners in oral examinations. Notwithstanding, advancements are still required to redesign the online learning environment for critical thinking in higher education.